Effective Cough Technique In Pulmonary Tb Patients With The Application Of Florance Nightingale Theory Application At The Kota Baru Health Center Of Lebong Regency In 2022 - Wulandari, Desti; Rustandi, Handi; Sofais, Danur Azissah roeslina (Universitas Dehasen Bengkulu, 2023)
Intoduction: Tuberculosis is an old disease that is still the most killer among infectious diseases, Pulmonary Tuberculosis (TB) will have a direct impact on sufferers, namely physical weakness, continuous cough, shortness of breath, chest pain, decreased appetite, weight loss, night sweats and high heat while the impact on families is untreated Pulmonary TB sufferers will transmit TB germs to their families, and it will be very difficult if TB sufferers live in one house with many people.The purpose of this study was to understand and apply nursing care Effective Cough Techniques in Pulmonary Tb Patients with the Application of Florance Nightingale Theory.This study uses a method that is a nursing process approach based on the chosen nursing theory, the techniques used in data collection are interviews, observations, physical examinations and conducting nursing care. The source of data obtained or used is primary obtained directly from patients and secondary data obtained from family, health workers and documentation from other examination results to carry out nursing care, while literature study is to study source books related to nursing care given to patients. Nightingale views nursing as a health science and elaborates nursing as directing towards the improvement and management of the physical environment so that nature will heal patients. Therefore, nursing activities include providing education on hygiene in the household and environment to help women create or create a healthy environment for their families and communities that basically aims to prevent disease.Where the purpose of nursing action is to maintain, prevent infection and injury, recover from illness, conduct health education and control the environment. The reason for nursing according to Florence Nightingale is to put humans in the best condition naturally to heal or improve health and prevent disease and injury